2019
DOI: 10.1186/s40543-019-0183-3
|View full text |Cite
|
Sign up to set email alerts
|

ZnO-TiO2 doped polyacrylonitrile nano fiber-Mat for elimination of Cr (VI) from polluted water

Abstract: PAN nanofiber-Mat (n-fib@Mat), PAN/ZnO n-fib@Mat, and PAN/ZnO-TiO 2 n-fib@Mat were prepared via electrospinning method. Their high adsorption capacities against dissolved Cr (VI) ions make them as super adsorbents for water treatment. The structure of n-fib@Mat was investigated using XRD, FTIR, SEM, and TEM techniques. The effects of selected parameters such as contact time, initial concentration, and n-fib@Mat amount were assessed in a fixed bed reactor. It was found that the adsorption capacities of PAN n-fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 34 publications
0
10
0
Order By: Relevance
“…Production of ZnO nanorods and nanosheets on nanofibers according to Zhu et al 30 PAN/ZnO/TiO 2 nanofiber mats could most rapidly adsorb the Cr(VI) ions from water. 39 ZnO was also suggested as part of a mixed matrix membrane, consisting from a PVA nanofiber mat on a functionalized cellulose-acetate substrate. The nanofiber mat was modified by embedding ZnO nanoparticles and sodium alginate.…”
Section: Applications Of Zno Nanofibersmentioning
confidence: 99%
“…Production of ZnO nanorods and nanosheets on nanofibers according to Zhu et al 30 PAN/ZnO/TiO 2 nanofiber mats could most rapidly adsorb the Cr(VI) ions from water. 39 ZnO was also suggested as part of a mixed matrix membrane, consisting from a PVA nanofiber mat on a functionalized cellulose-acetate substrate. The nanofiber mat was modified by embedding ZnO nanoparticles and sodium alginate.…”
Section: Applications Of Zno Nanofibersmentioning
confidence: 99%
“…Several works published adsorption of toxic metal ions was improved by incorporating NPs such as iron oxide, zinc oxide (ZnO), titanium dioxide, silicon dioxide (SiO 2 ), etc., into the electrospun nanofibrous adsorbents [ 22 , 23 , 24 , 25 ]. Makaremi et al [ 26 ] reported the improvement of the chromium ion removal efficiency by incorporating ZnO into polyacrylonitrile (PAN) nanofibrous adsorbents.…”
Section: Introductionmentioning
confidence: 99%
“…37 The modified polyacrylonitrile nanofibrous membranes owing to their larger surface area, resistance to chemicals, lower flammability, better mechanical properties, and thermal stability have been found to be efficient in PM2.5 filtration [11][12][13]38 as well as adsorption of heavy metal ions. 27,[39][40][41][42][43][44][45] The surface modification of PAN nanofibers results in its altered hydrophilicity and introduction of chelating groups, which in turn are responsible to make them suitable for efficient adsorption. 46,47 Clay minerals are hydrous aluminosilicates, which have been widely used for filtration applications.…”
Section: Introductionmentioning
confidence: 99%
“…One of the widely used polymers for electrospinning is polyacrylonitrile (PAN) due to its ease to spinnability, commercial availability, stability, and good mechanical properties 37 . The modified polyacrylonitrile nanofibrous membranes owing to their larger surface area, resistance to chemicals, lower flammability, better mechanical properties, and thermal stability have been found to be efficient in PM2.5 filtration 11–13,38 as well as adsorption of heavy metal ions 27,39–45 . The surface modification of PAN nanofibers results in its altered hydrophilicity and introduction of chelating groups, which in turn are responsible to make them suitable for efficient adsorption 46,47 …”
Section: Introductionmentioning
confidence: 99%